2021
DOI: 10.1096/fba.2021-00059
|View full text |Cite
|
Sign up to set email alerts
|

The butyrophilin 1a1 knockout mouse revisited: Ablation ofBtn1a1leads to concurrent cell death and renewal in the mammary epithelium during lactation

Abstract: Butyrophilin 1A1 (BTN1A1) is implicated in the secretion of lipid droplets from mammary epithelial cells as a membrane receptor, which forms a secretion complex with the redox enzyme, xanthine oxidoreductase (XDH). The first evidence that BTN1A1 functions in this process was the generation of Btn1a1−/− mouse lines, in which lipid secretion was disrupted and large unstable droplets were released into alveolar spaces with fragmented surface membranes. We have revisited one of these mutant mouse lines using RNAse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 89 publications
2
7
0
Order By: Relevance
“…Whether this cell-intrinsic JAK/STAT suppression is directly tied to the immune checkpoint activity of BTN1A1 remains unclear, but may be of clinical relevance given the essential role of JAK1-mediated signaling in IFN-mediated innate immunity 29 . Studies of BTN1A1 -/mice generated by a separate group have also suggested a role for this butyrophilin family member as a regulator of STAT3 signaling and inflammatory activity in the context of milk lipid droplet production 20 , potentially providing some degree of additional support for the present findings. Additional studies of endogenous BTN1A1 ligands and the relevance of this BTN1A1/JAK1 axis in oncogenic and immunological contexts are thus warranted.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Whether this cell-intrinsic JAK/STAT suppression is directly tied to the immune checkpoint activity of BTN1A1 remains unclear, but may be of clinical relevance given the essential role of JAK1-mediated signaling in IFN-mediated innate immunity 29 . Studies of BTN1A1 -/mice generated by a separate group have also suggested a role for this butyrophilin family member as a regulator of STAT3 signaling and inflammatory activity in the context of milk lipid droplet production 20 , potentially providing some degree of additional support for the present findings. Additional studies of endogenous BTN1A1 ligands and the relevance of this BTN1A1/JAK1 axis in oncogenic and immunological contexts are thus warranted.…”
Section: Discussionsupporting
confidence: 63%
“…While there is limited evidence that BTN1A1 may additionally be expressed in secondary lymphoid organs and can suppress T cell activation together with BTN2A2 19 , its regulatory role and clinical relevance in this context remain to be fully explored. BTN1A1 -/mice have also been developed, and recent systematic analyses of these animals have suggested that the loss of this butyrophilin family member is associated with enhanced inflammatory activity and activation of STAT3 signaling, further suggesting a potential regulatory role for BTN1A1 as a suppressor or immune-related and inflammatory response induction 20 . Given that BTN proteins serve as B7-related context-dependent immunosuppressive or immunostimulatory mediators, they represent promising candidate immune checkpoint proteins.…”
Section: Introductionmentioning
confidence: 99%
“…While moving intracellularly, CLDs interact with other organelles, including the Golgi apparatus, mitochondria and casein-containing secretory vesicles (Wooding 1971, Wooding 1973, Stemberger, Walsh et al 1984, Wu, Howell et al 2000, Mather, Jack et al 2001, Honvo-Houéto, Henry et al 2016). When they arrive at the apical cytoplasm, CLDs form contacts with the apical plasma membrane via interactions between CLD-coating Plin2, cytoplasmic xanthine dehydrogenase (Xdh; also known as xanthine oxidoreductase, Xor) and the transmembrane apical plasma membrane protein butyrophilin, subfamily 1, member A1 (Btn1a1) (Ishii, Aoki et al 1995, Keenan and Patton 1995, Mather and Keenan 1998, McManaman, Palmer et al 2002, Vorbach, Scriven et al 2002, Ogg, Weldon et al 2004, Robenek, Hofnagel et al 2006, Jeong, Rao et al 2009, Monks, Dzieciatkowska et al 2016, Jeong, Kadegowda et al 2021). These proteins and their interactions allow for tight tethering, or docking, of CLDs to the apical plasma membrane, where they can continue to grow by fusion and protrude into the alveolar lumen (Dylewski, Dapper et al 1984, Masedunskas, Chen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic disruption of the CLD synthetic machinery and docking complex components leads to poor offspring growth or starvation and death due to low milk consumption (Vorbach, Scriven et al 2002, Ogg, Weldon et al 2004, Russell, Schaack et al 2011, Wang, Lv et al 2012, Monks, Dzieciatkowska et al 2016, Zhao, Ke et al 2020, Jeong, Kadegowda et al 2021). Models targeting the CLD synthetic machinery drive low milk fat production and secretion, decreasing milk caloric content (Smith, Cases et al 2000, Beigneux, Vergnes et al 2006, Russell, Schaack et al 2011, Wang, Lv et al 2012, Suburu, Shi et al 2014), and models targeting the MFG secretion machinery drive the production of extremely large and unstable MFGs which potentially clog the ductal network, blocking overall milk secretion (Vorbach, Scriven et al 2002, Ogg, Weldon et al 2004, Monks, Dzieciatkowska et al 2016, Jeong, Kadegowda et al 2021). These mechanistic details have been worked out in dairy animals and/or model organisms by electron microscopy, immunohistochemistry & fluorescence and most recently, by elegant intravital imaging of glandular tissue (Mather, Masedunskas et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While moving intracellularly, CLDs can interact with other organelles, including the Golgi apparatus, mitochondria and casein-containing secretory vesicles ( Wooding, 1971 ; Wooding, 1973 ; Stemberger et al, 1984 ; Wu et al, 2000 ; Mather et al, 2001 ; Honvo-Houéto et al, 2016 ). When they arrive at the apical cytoplasm, CLDs form contacts with the apical plasma membrane via interactions between CLD-coating Plin2, cytoplasmic xanthine dehydrogenase (Xdh; also known as xanthine oxidoreductase, Xor) and the transmembrane plasma membrane protein butyrophilin, subfamily 1, member A1 (Btn1a1) ( Ishii et al, 1995 ; Keenan et al, 1995 ; Mather and Keenan, 1998 ; McManaman et al, 2002 ; Vorbach et al, 2002 ; Ogg et al, 2004a ; Robenek et al, 2006 ; Jeong et al, 2009 ; Monks et al, 2016 ; Jeong et al, 2021 ). These proteins and their interactions allow for tight tethering, or docking, of CLDs to the apical plasma membrane, where they can continue to grow by fusion and protrude into the alveolar lumen ( Dylewski et al, 1984 ; Monks et al, 2016 ; Masedunskas et al, 2017 ; Monks et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%